Rhinocerebral mucormycosis to the rise? The impact of the worldwide diabetes epidemic()() - Martínez-Herrera, Erick (An Bras Dermatol, 2021)
The authors present seven cases of rhinocerebral mucormycosis associated to diabetes mellitus, which is a disease with epidemic proportions affecting individuals worldwide, particularly in developing countries, and which poses significant morbidity and mortality. Mucormycosis is an opportunistic fungal infection with high mortality and requires an invasive therapeutic approach to save the patient’s life with significant morbidity and sequelae, thus prevention is crucial.